The determinant factors and homeownership intention among young people in Petaling Jaya, Selangor / Nur Farisya Ahmad Fadzil Sumbandy, Muhammad Arif Noor Ahmad and Mahazril 'Aini Yaacob - Ahmad Fadzil Sumbandy, Nur Farisya; Ahmad, Muhammad Arif Noor; Yaacob, Mahazril 'Aini (2021)
When it comes to owning a property, there are many challenges that an individual undergoes, not only to fresh graduates but to some of them who already have a family but are unable to own a home. The National Housing Policy (NHP) was introduced to ensure access to adequate and affordable shelter and related facilities for all Malaysians, especially low- income groups. Some of the programs are the affordable housing scheme for civil servants (PPAM), 1 Malaysia People Housing Programme (PR1MA), People Housing Program (PPR), and Private Affordable Housing Scheme (MyHome). Many determinant factors influence homeownership intention for young people, especially for those who live in urban areas. However, this research mainly focuses on the four elements: cost of living, housing prices, location, and role of financial institutions. Some of the past studies related to the determinants factor are that Malaysia is now facing a rising cost of living when the United Nations (UN) expert reports that the poverty rate in the world is massively underreported (Azril Annuar, 2019). The average house price in Malaysia has increased from RM 426,417 in 2019 to RM 427,882 in 2020 (National Property Information Center, 2020). Bank Negara Malaysia (BNM) found that specific terms and conditions in housing loans and finance contracts are unfairly biased in favour of banking institutions (Shankar, 2019). Monica (2018), in her study, revealed that location is one of the variables observed by individuals when considering a place to live. Based on the discussion, the study investigates the determinant factors that influence homeownership intention among young people in Malaysia, focusing on young people in Petaling Jaya.